Police officers' perceptions of the challenges involved in Internet Child Exploitation investigation. Issue 3 (12th August 2014) - B. Powell, Martine; Cassematis, Peter; S. Benson, Mairi; Smallbone, Stephen; Wortley, Richard
Abstract : Purpose: – The purpose of this paper is to explore police officers' perceptions of the challenges and work stressors of working in Internet Child Exploitation (ICE) investigation. Design/methodology/approach: – Participants were a heterogeneous sample of 32 ICE investigators across nine Australian jurisdictions. Officers' perceptions of ICE work were elicited via individual, open-ended, anonymous, telephone interviews, which focused on both the nature and impact of work-related stressors and challenges. Findings: – Thematic analysis revealed that viewing ICE material was not perceived to be a major stressor or particularly traumatic facet of ICE investigation. Rather, the challenges related to three areas; work relationships, workload and resources and the physical environment. Participants also suggested some improvements to their work environment which could reduce the impact of these challenges. Practical implications: – The stressors identified by ICE investigators in this study place physical, psychological and social restrictions on investigative capacity. Modifications to the workplace environment that facilitate more effective professional collaboration, reduce workload and enhance investigator efficiency and functionality of the physical work environment would likely reduce the potential for harm associated with ICE investigation and improve ICE investigators' capacity to perform their role. Originality/value: – This is the first study to use a broad research framework to examine the full range of stressors that ICE investigators face (both organisational and operational). The findings are important for developing comprehensive theories regarding workplace traumatisation as well as holistic intervention models to assist the prevention and management of stress related to ICE investigation.